Impacto do descomissionamento da barragem Monjolinho sobre a ictiofauna, bacia do alto Paraná - Gattis, Vitória Cecatto (2025)
The Monjolinho Stream, impounded by a small dam on the campus of the Federal University of São Carlos, where there is already a historical context of pollution, has been the subject of several studies across different fields and for various purposes. Its reservoir underwent multiple interventions and was completely drained in 2019 due to structural issues with the dam. Over the years, this environment had supported the establishment of a biotic community characteristic of a lentic system. The draining of the reservoir restored the original lotic flow, clearly imposing a new restructuring of the resident aquatic communities. Based on this recent history, the aim of this study was to gather information on dam decommissioning worldwide and to investigate the composition of the ichthyofauna with a focus on its spatial and temporal distribution in the Monjolinho Stream, as well as to assess possible changes in trophic relationships imposed by the new environmental conditions. To this end, fish were collected both upstream and downstream in 2019 (before decommissioning) and again in 2023 and 2024 (after decommissioning). Water samples were also collected for analysis of selected physical and chemical variables. Fish sampling was conducted in 50-meter stretches located upstream and downstream, using single-pass electrofishing in a downstream-to-upstream direction and 10 casts of a throw net in the semi-lentic section of the stream. Simpson diversity and Bray–Curtis dissimilarity indices were calculated to assess changes in the ichthyocenosis between study periods. A Non-metric Multidimensional Scaling (NMDS) analysis was performed on the species community structure, considering two regions (upstream and downstream) with three sampling periods at each site (2019, 2023, and 2024). An environmental variable fitting analysis (envfit) revealed turbidity as the environmental variable most strongly associated with the NMDS ordination. This variable showed a coefficient of determination (r²) of 0.9541 with a p-value < 0.05. Our results indicate dissimilarity in the ichthyofauna before and after decommissioning, especially concerning lentic species, due to habitat alteration and its impact on reproduction.